Assembly of Clay Nanotubes on Cotton Fibers Mediated by Biopolymer for Robust and High‐Performance Hemostatic Dressing (Adv. Healthcare Mater. 1/2023). Issue 1 (2nd January 2023) - Feng, Yue; He, Yunqing; Lin, Xiaoying; Xie, Mingyang; Liu, Mingxian; Lvov, Yuri
Abstract : Clay‐Based Robust Hemostats In article 2202265 by Mingxian Liu, Yuri Lvov, and co‐workers, an efficient clay hemostat of halloysite nanotubes is tightly assembled onto cotton fibers and capillaries mediated by a biopolymer alginate with Ca 2+ crosslinking. This dressing maintains high clotting activity after washing and only a few residuals in the wound. This strategy balances the robustness, biosafety, and effectiveness of composite wound dressing.